2021
DOI: 10.3390/ijgi10080521
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Temporal Changes of Inland Ramsar Sites in Turkey Using Google Earth Engine

Abstract: Ramsar Convention (RC) is the first of modern intergovernmental agreement on the conscious use and conservation of natural resources. It provides a platform for contracting parties working together to develop the best available data, advice, and policy recommendations to increase awareness of the benefits of wetlands in nature and society. Turkey became a party of the RC in 1994, and in the years 1994 to 2013, 14 wetlands that reached the Ramsar criteria were recognized as Ramsar sites (RS). With this study, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…• C. According to the data of 249 stations throughout Turkey, the increase in air temperature is about 2 • C in the past thirty-five years [55,56]. In this study and the previous study [4], it was observed that an increase of approximately 2 degrees in temperature over a thirtyfive-year period causes a decrease in inland wetlands. Climate change studies project that temperatures in Turkey will increase by 0.5 to 3.0 • C by 2050, and 0.5 to 4.0 • C by 2100, with an optimistic scenario (RCP 4.5).…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…• C. According to the data of 249 stations throughout Turkey, the increase in air temperature is about 2 • C in the past thirty-five years [55,56]. In this study and the previous study [4], it was observed that an increase of approximately 2 degrees in temperature over a thirtyfive-year period causes a decrease in inland wetlands. Climate change studies project that temperatures in Turkey will increase by 0.5 to 3.0 • C by 2050, and 0.5 to 4.0 • C by 2100, with an optimistic scenario (RCP 4.5).…”
Section: Resultssupporting
confidence: 60%
“…Each Ramsar site meets at least one of the nine criteria [3] related to wetland types, ecological communities, water birds, fish, and other taxa, that signify international importance. In the previous study [4], all inland Ramsar sites in Turkey were examined from 1985 to 2020, and changes in water surface areas were evaluated on the Google Earth Engine (GEE) cloud computing platform, using Landsat satellite images and the Normalized Difference Water Index (NDWI). Data acquired from the closest meteorological stations to each Ramsar Site were evaluated, and in addition to the meteorological effects, the other factors that may have been causing changes in these areas were also investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Because of drought and misuse of water resources, half of Türkiye's inland water bodies have lost their ecological and economic qualities for the past 40 years [29]. The main threats to inland water bodies in Türkiye, which are the primary causes of the loss, include unplanned water infrastructure projects such as dams built on rivers feeding lakes, in addition to inter-basin water transfers, excessive irrigation use in agriculture, pollution, illegal hunting and fishing, and other large-scale investments such as highways [30]. The RS data have been used to examine Türkiye's inland water bodies, as well.…”
Section: Introductionmentioning
confidence: 99%
“…Gozukara et al [32] utilized Landsat imageries and determined that Lake Burdur's water level decreased by 13.74 m (−2%) and the lake surface area decreased from 211 km 2 to 130 km 2 (−38.39%) over 42 years (1975-2017). Additionally, Dervisoglu [30] assessed the temporal changes in Türkiye's inland Ramsar sites using Landsat satellite images and the NDWI. It was discovered that inland wetlands declined at varying rates between 1985 and 2020.…”
Section: Introductionmentioning
confidence: 99%
“…Among the various remote sensing indices, NDWI (Normalized Difference Water Index) is one of the most water practical indices used in many studies to track and predict wetland hydrological changes [37][38][39][40]. In addition, NDVI (Normalized Difference Vegetation Index) has been used as a vegetation indicator to investigate changes in vegetation conditions [33,41].…”
Section: Introductionmentioning
confidence: 99%